Key Uncertainties in the Recent Air‐Sea Flux of CO2. Issue 12 (6th December 2019) - Woolf, D.K.; Shutler, J.D.; Goddijn‐Murphy, L.; Watson, A.J.; Chapron, B.; Nightingale, P.D.; Donlon, C.J.; Piskozub, J.; Yelland, M.J.; Ashton, I.; Holding, T.; Schuster, U.; et al.
Abstract: The contemporary air‐sea flux of CO2 is investigated by the use of an air‐sea flux equation, with particular attention to the uncertainties in global values and their origin with respect to that equation. In particular, uncertainties deriving from the transfer velocity and from sparse upper ocean sampling are investigated. Eight formulations of air‐sea gas transfer velocity are used to evaluate the combined standard uncertainty resulting from several sources of error. Depending on expert opinion, a standard uncertainty in transfer velocity of either ~5% or ~10% can be argued and that will contribute a proportional error in air‐sea flux. The limited sampling of upper ocean f CO2 is readily apparent in the Surface Ocean CO2 Atlas databases. The effect of sparse sampling on the calculated fluxes was investigated by a bootstrap method, that is, treating each ship cruise to an oceanic region as a random episode and creating 10 synthetic data sets by randomly selecting episodes with replacement. Convincing values of global net air‐sea flux can only be achieved using upper ocean data collected over several decades but referenced to a standard year. The global annual referenced values are robust to sparse sampling, but seasonal and regional values exhibit more sampling uncertainty. Additional uncertainties are related to thermal and haline effects and to aspects of air‐sea gas exchange not captured by standard models. An estimate of global net CO2 exchange referenced to 2010 of −3.0 ± 0.6 Pg C/year is proposed, where the uncertainty derives primarily from uncertainty in the transfer velocity. Plain Language Summary: The oceanic carbon sink reduces the rate of accumulation of CO2 in the atmosphere but is also responsible for the acidification of the ocean. One method of estimating the size of the oceanic carbon sink depends on a calculation of upward and downward flows of CO2 at the sea surface. This study revisits this calculation using updated knowledge of the transfer processes at the sea surface and the results of a large international collaborative effort (Surface Ocean CO2 Atlas) to collect and compile measurements of CO2 in the upper ocean. Greater sampling of the oceans improves estimates, but direct calculation in each year is not practical. Instead, we calculate fluxes in a recent year (2010) using upper ocean measurements of CO2 over many years. The remaining uncertainty is dominated by limited knowledge of the efficiency of stirring of gas across the sea surface, the air‐sea transfer velocity. The study suggests a relatively large downward flow of CO2 into the ocean compared to previous applications of this method and other methods to estimate the oceanic carbon sink. Increased knowledge is rewarded by reduced uncertainty in the net global flux; that flux is estimated at −3.0 ± 0.6 Pg C/year. Further understanding of transfer velocities and better sampling may reduce the uncertainty in the future. Key Points: Increased understanding of air‐sea gas transfer processes and better sampling of the upper ocean enables higher confidence in calculations of air‐sea CO2 fluxes The calculations imply a relatively large global net air‐to‐sea flux of −3.0 Pg C/year (referenced to 2010) This flux is known within 0.6 Pg C/year, where uncertainty in air‐sea transfer velocity is the largest contribution to the combined uncertainty